TIPS FOR WRITING CRISP AND FUN ARTICLES; READY TO MARRY FOR TEENAGERS IN THE CONCEPT OF LITERACY - Lili Perpisa; Zulkifli Zulkifli; Weni Yulastri; Febrina Riska Putri (RANGKIANG: Jurnal Pengabdian Pada Masyarakat, 2024)
Adolescents as individuals have readiness and planning to start a family which can be expressed in the form of scientific work. The problem that arises among some teenagers is the lack of ability of teenagers to express their ideas and thoughts about family readiness and planning in the form of scientific work. The aim of the activity is to improve teenagers' understanding and skills regarding the rules for writing scientific papers, especially mastery of material, article writing skills and skills in exploring references in writing scientific papers about family readiness and planning. The activity method is carried out through technical assistance through classical, individual and group approaches. The informants were teenagers under the guidance of the Youth Resilience Working Group of the West Sumatra Province BKKBN Representative Office. Data was collected through interviews and documentation, then processed qualitatively with a descriptive approach. Based on the evaluation results, it can be stated that this activity has been carried out well and smoothly. This can be seen from the enthusiasm of the participants in participating in the activity and the number of articles that have been provided with improvement consultation services. Through technical assistance activities, teenagers can master the material and have the skills to write scientific articles related to family readiness and planning, as well as have the skills to access references and journals with indicators of youth participation in exploring references from various articles and participation in studying the journals where the articles are published. Problems that occur internally and externally have also been addressed with a number of actions and input. Adopting technical assistance in writing scientific papers for activities with different substance is highly recommended unless there are significant differences in participant characteristics.